Antibacterial Activity Test Against Cutibacterium acne and Contaminant Testing of Spirulina (Arthrospira platensis) Anti-Acne Serum - Hilma Putri; Phebe Hendra (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Acne is a skin problem caused by the Cutibacterium acne bacteria, which has increasing bacterial resistance. Therefore, this study aims to evaluate the antibacterial activity of spirulina extract serum against C. acne, as well as to test for microbial contamination, heavy metals, and microplastics in the serum. Antibacterial activity tests were conducted using the well diffusion method with varying concentrations of spirulina extract (0.25%, 0.5%, and 1%) compared to the positive control clindamycin. Microbial and heavy metal contamination tests were conducted based on standard laboratory methods. Verify microplastic-free status using the "Beat the Microbead" app. The test results show that spirulina extract does not produce a significant inhibition zone. However, after being formulated into a serum, there is an increase in antibacterial activity classified as strong, with an average largest inhibition zone diameter of 16.27 ± 0.25 mm. Contamination testing shows that the serum meets Indonesian Food and Drug Authority cosmetic safety requirements, is free from the Total Plate Count, Mold and Yeast Count, pathogenic microbes, and heavy metals within permissible limits. The microplastic test also showed that the serum does not contain microplastics, with the scanning results appearing green. In conclusion, spirulina extract serum has antibacterial activity and potential as a safe and environmentally friendly anti-acne product.